Socio-economic condition of goat farmers and management practices of goats in selected areas of Munshiganj district of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
A total of 100 respondents were randomly selected to assess the socio-economic condition and management practices of goat rearing in Munshiganj district of Bangladesh. Data were collected through interviewing with pre-tested questionnaires from July to December, 2017. The result revealed that most of the goat keepers were middle aged and illiterate. Agricultural crop farming (47.0%) was the main occupation. Majority of the farmers kept their goats on their own land for at least 2 years (44.0%). Sixty percent of the farmers used own capital and rest of them took loan from bank/or NGO’s loan for rearing goats. The highest numbers of goats were found Black Bengal (55.0%) followed by Crossbred (24.0%) and Jamnapari goat (21.0%) reared mainly for meat purpose (80.0%) in semi-intensive farming system. In this study area, the average birth weight of kid was 0.91 kg and market weight 16.5 kg. Weaning and slaughter age were 4 and 18 months, respectively. The average age at 1st heat, gestation period, post-partum heat period, average prolificacy and kidding interval was 7.4 months, 5.1 months, 45.5 days, 2.1 kids per kidding and 8.5 months, respectively. Fifty four percent of respondents reported that their goats were mated by using a buck belonging to other farmers; the cost was Tk. 20-30 per mating. The farmers fed their goats with locally available roughages and tree leaves in the selected areas. Some goat farmers (5.0%) were practicing to supply concentrate feeds to their goats. The results showed that family member’s especially young women and children (67.0%) are more likely to own and raise small ruminants. They did not follow any vaccination and de-worming programme.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (2), 150-155